Factors That Contribute to The Image of Digital Platforms: Meta-Synthesis - Ulfa, Chairia (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study aims to identify the main factors that affect the image of the digital economy platform, analyze its impact, and provide recommendations for platform managers. From a meta-synthesis of 57 scientific journals from 2020-2024, four main variables were found: trust and reputation, user experience, security and privacy, and responsiveness and customer support. The results show that platform trust, positive user experience, data protection, and responsive customer support are the keys to forming a positive image. The implication for platform maintainers is to focus on improving service quality, maintaining data security, and providing responsive customer support. These four factors are interrelated and need attention to strengthen the image of the platform in the eyes of users. This research adds insight to the academic literature and provides practical guidance and policy recommendations to support the development of a healthy and sustainable digital economy platform.